Cerebral Extracellular Lactate Increase is Predominantly Nonischemic in Patients with Severe Traumatic Brain Injury. Issue 11 (November 2013) - Sala, Nathalie; Suys, Tamarah; Zerlauth, Jean-Baptiste; Bouzat, Pierre; Messerer, Mahmoud; Bloch, Jocelyne; Levivier, Marc; Magistretti, Pierre J; Meuli, Reto; Oddo, Mauro
Growing evidence suggests that endogenous lactate is an important substrate for neurons. This study aimed to examine cerebral lactate metabolism and its relationship with brain perfusion in patients with severe traumatic brain injury (TBI). A prospective cohort of 24 patients with severe TBI monitored with cerebral microdialysis (CMD) and brain tissue oxygen tension (PbtO2 ) was studied. Brain lactate metabolism was assessed by quantification of elevated CMD lactate samples (>4 mmol/L); these were matched to CMD pyruvate and PbtO2 values and dichotomized as glycolytic (CMD pyruvate > 119 μmol/L vs. low pyruvate) and hypoxic (PbtO2 < 20 mm Hg vs. nonhypoxic). Using perfusion computed tomography (CT), brain perfusion was categorized as oligemic, normal, or hyperemic, and was compared with CMD and PbtO2 data. Samples with elevated CMD lactate were frequently observed (41 ±8%), and we found that brain lactate elevations were predominantly associated with glycolysis and normal PbtO2 (73 ± 8%) rather than brain hypoxia (14 ±6%). Furthermore, glycolytic lactate was always associated with normal or hyperemic brain perfusion, whereas all episodes with hypoxic lactate were associated with diffuse oligemia. Our findings suggest predominant nonischemic cerebral extracellular lactate release after TBI and support the concept that lactate may be used as an energy substrate by the injured human brain.